Purchasing and supply chain management : strategies and realities - Quayle, Michael, 1947- (Hershey, PA : Idea Group Publ., 2006)
'This book shows readers how to develop supply chain strategy and implementation and use it gain an advantage in the 21st century competitive marketplace'--Provided by publisher.
Includes bibliographical references and index
Keywords: Business logistics -- Management; Strategic planning